Effects of floor impact noise on psychophysiological responses. (1st May 2017) - Park, Sang Hee; Lee, Pyoung Jik
Abstract: The present study analysed the effects of floor impact noise on humans using both psychological and physiological methods. Floor impact noises caused by a standard impact source (i.e. impact ball) and five real impact sources (e.g., human footsteps and dropped objects) were recorded as sound stimuli. During the laboratory experiments, two factors that impact psychophysiological responses were considered: (1) types of impact sources (standard or real sources) and (2) the levels of floor impact noise ranging from 31.5 to 63 dBA in terms of A-weighted maximum sound pressure level ( L AFmax ). Twenty-one normal-hearing subjects were then asked to judge the noticeability and annoyance caused by the floor impact noises. Meanwhile, the subjects' physiological responses (heart rate: HR, electrodermal activity: EDA, and respiration rate: RR) were monitored throughout the experiments. Noise annoyance and noticeability increased with increases in noise levels, the impact ball resulted in higher noticeability and annoyance ratings than real sources. All physiological measures varied significantly with noise exposure; HR decreased, whereas EDA and RR increased. The results show that the physiological responses were not affected by the type of noise source. In addition, the noise level was found to be significantly related to EDA and RR changes, whereas the relationship between the noise level and HR was not found to be significant. Highlights: Noise annoyance and noticeability increased with increases in noise levels. Physiological measures (HR, EDA, and RR) varied significantly with floor noise exposure. Physiological responses were not affected by the type of noise source (standard or real sources). The noise level was found to be significantly related to EDA and RR changes.